Nutrition and Quality Properties of Low-calorie Cake Made by Low-calorie Fat Formula (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
The present study was conducted to produce a low-calorie fat (LCF) characterized by normal specification of commercial fat and acceptable quality properties, to be used in making low calorie cakes with Low-calorie fat. The low- calorie fat formulated by blending of beeswax and sunflower oil in three different ratios (25:75, 50:50, 75:25) w/w. The physiochemical properties of Low-calorie fat and nutritional, caloric and sensory properties of prepared cakes were evaluated. The properties of melting point and peroxide value are significantly increased (P≤ 0.05) for the three formulated fats. While the values of free fatty acids and acid value, their values are higher in A25:75 and C 75:25 samples as compared with B 50:50 sample. Inversely, the blending level of 25:75 had a higher smoke point score. The sensory properties of prepared cakes all are  insignificant (p>0.05) for control A, B and C samples in terms of Taste, Favor, Crumb color, Crumb softness, texture and overall score. A nutritional content sash, protein, carbohydrate, caloric value, caloric decreasing percentage values are significantly (P≤ 0.05) influenced by control, A, B and C samples. The caloric value of all cake samples is significantly (P≤ 0.05) decreased with respect to control sample.